2019
DOI: 10.1007/s00062-019-00795-z
|View full text |Cite
|
Sign up to set email alerts
|

The ReWiSed CARe Technique

Abstract: Background Endovascular treatment of acute cerebral large vessel occlusions and concomitant atherosclerotic lesions of the ipsilateral internal carotid artery (ICA) are a matter of debate. This article reports a multi-center experience using the retriever wire supported carotid artery revascularization (ReWiSed CARe) technique allowing simultaneous treatment of both lesions. Methods The study retrospectively analyzed 23 patients with acute tandem occlusions (TO) who underwent ReWiSed CARe at 3 German centers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The debate regarding the order of stent placement relative to thrombectomy has recently been circumvented by some authors who have developed techniques using nearly simultaneous c-ICA revascularization and intracranial stent-retriever thrombectomy; however, adoption of this approach remains limited thus far. 29,30 What Type of Stent Should Be Used? Dual-layer stents contain a second micromesh layer to theoretically better cover the atherosclerotic plaque and more effectively prevent dislodgement of debris.…”
Section: Should the Intracranial Or Extracranial Lesions Be Treated Fmentioning
confidence: 99%
“…The debate regarding the order of stent placement relative to thrombectomy has recently been circumvented by some authors who have developed techniques using nearly simultaneous c-ICA revascularization and intracranial stent-retriever thrombectomy; however, adoption of this approach remains limited thus far. 29,30 What Type of Stent Should Be Used? Dual-layer stents contain a second micromesh layer to theoretically better cover the atherosclerotic plaque and more effectively prevent dislodgement of debris.…”
Section: Should the Intracranial Or Extracranial Lesions Be Treated Fmentioning
confidence: 99%
“…Steno-occlusion of the cervical internal carotid artery (ICA) poses a technical challenge in the treatment of TO by endovascular means [ 6 ]. Emergent stenting of the extracranial carotid lesion is a predictor of successful reperfusion and favourable outcome in this complex patient population [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ideal endovascular treatment of acute cerebral large vessel occlusions and concomitant atherosclerotic lesions of the ipsilateral internal carotid artery (ICA) is still a matter of debate [ 5 ]. Recent retrospective multicentre studies have shown good results with simultaneous treatment of both occlusions with a good outcome (mRS 0–2) in up to 55% of patients [ 6 8 ]. Furthermore, a pooled analysis of the retrospective international TITAN trial and the prospective multicenter observational ETIS registry showed that acute cervical ICA stenting is associated with higher odds of favourable clinical outcome and successful reperfusion in patients with ischaemic strokes due to TO [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of TL treatment utilizing the SR’s wire, as in our procedure, include the method by Yamamoto et al 8) and the retriever wire supported carotid artery revascularization (ReWiSed CARe) technique by Behme et al 9 , 10) Compared with these techniques, our procedure has two important characteristics. One is the use of the Solitaire 6 × 40 mm, which is the longest SR, and the second is completion of the procedure under continuous balloon occlusion of the CCA with concomitant manual aspiration.…”
Section: Discussionmentioning
confidence: 99%